CASE REPORT: CLINICAL SINGS LESIONS OF BLACK BAG DISEASE OF SARCOTACES SPР. (COPEPODA, PHILICHTHYIDAE) INFESTATION CROPPER FISH EPINEPHELUS TAUVINA IN NORTHWEST ARABIAN GULF - T. Mohamed Essa (Российский паразитологический журнал, 2019)
Sarcotaces sp . (copepods), which infest and some the clinical sings lesions in cropper fish Epinephelus tauvina were register in Northwest Arabian Gulf. In March and June 2016, a total of 8 fish freshly collected from Al-Fao market South of Al-Basra City, northwest Arabian Gulf, Iraq. One of fish only infested with Sarcotaces sp. infested with Black Bag Disease with prevalence percentage 12.5 % Fish infected with Sarcotaces sp. showed no any clinical abnormalities and appeared to be completely normal. A new host and new geographical distribution for this copepod parasite in the fish of the Iraqi marine waters of the Arabian Gulf